CONCEPTUAL MODEL OF AN IT-SOLUTIONS FOR PATENT RESEARCH AUTOMATION - N. A. Kashevarova (Publishing House of the State University of Management, 2020)
The article is devoted to the development of a conceptual model patent of the patent analytics module integrated into the SAP corporate information system. It has been shown that patent research plays an important role in the strategic development of an enterprise based on the study of market trends. It has been proven that since the future strategy of the company depends on such a large dataset and the person is not able to assess the situation efficiently and consider a broad introduction, reengineering of the process of data collection and analysis is required, on which the fate of the enterprise depends. The primary purpose of this module is to provide automation of this kind of analysis and planning of strategic development of the enterprise. Moreover, the information collected by the system will help to correctly allocate funds for research and development programs.